Mitochondrially localised MUL1 is a novel modulator of antiviral signaling. Issue 4 (12th February 2013) - Jenkins, Kristie; Khoo, Jing Jing; Sadler, Anthony; Piganis, Rebecca; Wang, Die; Borg, Natalie A; Hjerrild, Kathryn; Gould, Jodee; Thomas, Belinda J; Nagley, Phillip; Hertzog, Paul J; Mansell, Ashley
Abstract : The innate immune response to virus must be balanced to eliminate infection yet limit damaging inflammation. A critical arm of the antiviral response is launched by the retinoic acid‐inducible‐gene I (RIG‐I) protein. RIG‐I is activated by viral RNA then associates with the mitochondrial antiviral signaling (MAVS) protein to subsequently induce potent inflammatory cytokines. Here, we demonstrate the mitochondrial E3 ubiquitin protein ligase 1 (MUL1) is a crucial moderator of RIG‐I signaling. MUL1 is localized to the mitochondria where it interacts with MAVS and catalyzes RIG‐I post‐translational modifications that inhibit RIG‐I‐dependent cell signaling. Accordingly, depletion of MUL1 potentiated RIG‐I mediated nuclear factor‐kappa B (NF‐κB) and interferon (IFN) β reporter activity. Moreover, depletion of MUL1 boosted the antiviral response and increased proinflammatory cytokines following challenge with the RNA mimetic poly I:C and Sendai virus. We therefore submit that MUL1 is a novel regulator of the RIG‐I‐like receptor‐dependent antiviral response, that otherwise functions to limit inflammation.